Assessment of Self Archiving in Digital Repositories: Is there any Difference between Science and Agriculture Scholars? - Gunasekera, Chamani (Journal of Information and Knowledge, 2018)
This study examines the differences in scholarly publishing and self-archiving practices of academic scholars in the faculties of agriculture and science in University of Peradeniya, Sri Lanka. Survey method was adapted and a questionnaire specifically designed was used to achieve the objectives of the study. The study population consisted of all permanent academic staff in the two faculties. The study established that majority of the respondents of both faculties were aware of self-archiving concept as a means for providing open access but not many of them had experience in self-archiving. Majority of respondents from both faculties began this activity two to three years ago and they learnt about self-archiving by working in a field with established subject based archives. The original motivators for self-archiving were self motivation and declared citation advantage of open access papers. Agriculture scholars deposited more full text articles in digital repositories than science scholars. When analyzing the results of this study, it was proved that most of the scholars in agriculture faculty preferred to deposit conference papers while science scholars mostly preferred preprint materials. PDF is the most preferred file format to deposit in the digital repositories.